Heroin assisted treatment and research networks. Issue 4 (7th December 2015) - Houborg, Esben; Andersen, Rasmus Munksgaard
Abstract : Purpose: – The purpose of this paper is to map research communities related to heroin-assisted treatment (HAT) and the scientific network they are part of to determine their structure and content. Design/methodology/approach: – Co-authorship as the basis for conducting social network analysis with regard to degree, weighted degree, betweenness centrality, and edge betweenness centrality. Findings: – A number of central researchers were identified on the basis of the number of their collaborative relations. Central actors were also identified on the basis of their position in the research network. In total, 11 research communities were constructed with different scientific content. HAT research communities are closely connected to medical, psychiatric, and epidemiological research and very loosely connected to social research. Originality/value: – The first mapping of the collaborative network HAT researchers using social network methodology.